2004
DOI: 10.1007/s00267-003-0030-5
|View full text |Cite
|
Sign up to set email alerts
|

Operational Atmospheric Modeling System CARIS for Effective Emergency Response Associated with Hazardous Chemical Releases in Korea

Abstract: The Chemical Accidents Response Information System (CARIS) was developed at the Center for Chemical Safety Management in South Korea in order to track and predict the dispersion of hazardous chemicals in the case of an accident or terrorist attack involving chemical companies. The main objective of CARIS is to facilitate an efficient emergency response to hazardous chemical accidents by rapidly providing key information in the decision-making process. In particular, the atmospheric modeling system implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…It embeds an array of standard models covering fire and explosion, multi-component evaporation, building infiltration and exfiltration, tank and pipe, dispersion, complex terrain. The Chemical Accidents Response Information System (CARIS) was developed at the Center for Chemical Safety Management in South Korea (Kim et al, 2004). This system also content a set of Dispersion and Air Quality Modelling (DAQM), including SLAB (Atmospheric Dispersion Model for Denser-Than-Air Gas), ALOHA (Areal Locations of Hazardous Atmospheres), VCE (Vapor Cloud Explosion) and so on.…”
Section: Many Researchmentioning
confidence: 99%
“…It embeds an array of standard models covering fire and explosion, multi-component evaporation, building infiltration and exfiltration, tank and pipe, dispersion, complex terrain. The Chemical Accidents Response Information System (CARIS) was developed at the Center for Chemical Safety Management in South Korea (Kim et al, 2004). This system also content a set of Dispersion and Air Quality Modelling (DAQM), including SLAB (Atmospheric Dispersion Model for Denser-Than-Air Gas), ALOHA (Areal Locations of Hazardous Atmospheres), VCE (Vapor Cloud Explosion) and so on.…”
Section: Many Researchmentioning
confidence: 99%
“…Such an approach can be used to assess the environmental safety of new industrial technologies [10], [11] along with an assessment of their economic efficiency [12]. Mathematical modelling of the physical processes of release and dispersion of harmful impurities in the surface layer of the atmosphere allows us to predict the fields of mass concentration of TC [13], to determine the inhalation toxidosis and the probability of damage to the maintenance personnel [14]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…In order to mitigate the damage of a chemical accident, a great deal of research has focused on the statistical analysis of accident risk [ 2 ] and executive emergency response plans [ 4 , 5 ]. With the development of environmental numeric simulation models [ 6 , 7 , 8 , 9 ] and model integration techniques [ 10 , 11 ], many Decision Support Systems (DSSs) have been established to help manage chemical hazards [ 12 , 13 , 14 , 15 , 16 , 17 ]. A recent survey found that most DSS are based on quantitative risk assessments of potential accident sources and used to predict and prevent major accidents.…”
Section: Introductionmentioning
confidence: 99%
“…However, limited by the technical capacity and design idea, these DSSs always have shortcomings in some respects. First the majority of DSSs can only handle specific types of accidents, mostly hazard release and diffusion [ 13 , 15 , 16 ]. Few take explosion and conflagration into consideration, but due to the serial simulation strategy, cannot realize the multi-type simulation simultaneously [ 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation